An exploration of the perceptions of young unemployed graduates in Lusaka, Zambia, of the factors contributing to their unemployment - Mungule, Maureen (Department of Social Development, 2017)
Among the problems that youth face, youth unemployment is more pronounced (Moleke, 2005; Annamária, 2013). Exclusion of youth from participating in the economy affects their wellbeing, and that of society. The objective of this study was, therefore, to explore the perceptions of young unemployed graduates in Lusaka, Zambia, of the factors contributing to their unemployment. To achieve the objective of the study, a qualitative research study was conducted with 20 unemployed tertiary level youth graduates in the field of humanities and arts studies. A qualitative study helped to gain an understanding on how the unemployed youth graduates interpreted their daily experiences and the meaning they gave to their status of being unemployed. Meanwhile, Tesch's eight-step approach for data analysis was employed. The study revealed that although the participants were actively job-seeking, a mis-match between their qualification and labour market skills demand; dependence on a formal or public sector post; lack of career guidance; lack of work experience; lack of social connections in the labour market; lack of merit based job recruitment practices which then promoted nepotism and corruption; lack of employment opportunities due to low levels of economic growth and high retirement age policy; and the unsuccessful government policies and programmes to promote self–employment through entrepreneurship skills and start-up capital for selfemployment, were believed by the graduate participants to be the factors contributing to graduate youth unemployment. The study also revealed that exclusion of youth from employment affects the social and economic wellbeing of not only the unemployed youth themselves but also their family. In this study, it was further revealed that the youth, the government, and the NGOs and the private sector, have roles to play in promoting youth graduate employment. The researcher in this study recommended that there was a need for youth graduates to be willing to venture into self-employment, to continue to demand for their right to employment opportunities from various stakeholders, to take responsibility to inform themselves about the existing government programmes and projects that relate to their employment, and to seek career guidance before embarking on their studies. On the part of government, they were to sensitize the graduate youth on and promote access to programmes that promoted youth employment, to provide and promote equal access to employment opportunities in all the sectors of the economy, to improve the macro-economic policies to attract foreign investment, to promote economic growth, to be able to conduct monitoring and evaluation of internship programmes, and to inculcate an entrepreneurship spirit and skills in the youth of the country. The NGOs and the private sector needed to continue playing their role of promoting and also providing employment for the youth through empowerment and providing skills development opportunities through internships, and to improve partnership with government.